PENGARUH PENERAPAN GOOD SCHOOL GOVERNANCE TERHADAP EFEKTIVITAS PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH - Dewi, Mike Kusuma; Ningsi, Sepri Hati; Meirina, Elsa; Annisa, Annisa; Septiana, Gina (Fakultas Ekonomi dan Bisnis Universitas Bung Hatta, 2025)
This study aims to analyze the influence of Good School Governance principles on the effectiveness of School Operational Assistance (BOS) fund management at Senior High School 11 Padang. The principles examined include participation, transparency, and accountability. The research employs a quantitative approach with a census method, encompassing the entire population of 75 respondents, consisting of the school principal, vice principals, treasurers, teachers, administrative staff, and school committee members. Research findings indicate that the principle of participation has a positive and significant effect on the effectiveness of BOS fund management with a regression coefficient of 0.2865 and p-value of 0.008 (p < 0.05). Meanwhile, the principles of transparency and accountability do not demonstrate statistically significant effects, with regression coefficients of 0.2232 (p-value 0.174) and 0.2020 (p-value 0.252), respectively. After that. At Senior High School 11 Padang. strengthen stakeholder participation and enhance transparency and accountability mechanisms in BOS fund management, despite the statistical insignificance of these two variables.